(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
Traditionally, constitutional revisions in the Soviet Union were conducted always using the same times and methods, as a ritual. Nevertheless, the approval of the 1993 Constitution followed a different path. This is not the case for the 2020 constitutional reform, which has significantly affected the whole Constitution. While presenting innovative variations, it still retraced fundamental passages of the URSS’s tradition, applying a mixed procedure that included both “amendments” and “revisions”.